Keputusan Pembelian Pada Instagram Pilihmentor.Com: Penelitian Pada Experiential Marketing Dan Content Marketing - A'limah, Nur; Yusiana, Rennyta (Akademi Sekretari Manajemen Taruna Bakti, 2024)
Businesses in the modern era or those that are popular with startups are growing. Efforts to overcome the problem of inequality in business assistance with the development of startups are the main mission of pilihmentor.com. One of the media that supports pilihmentor.com in carrying out its main mission is Instagram. The researcher, in this case, wants to know the purchasing decisions on Instagram pilihmentor.com which are influenced by Experiential Marketing and Content Marketing variables. The research method used is descriptive quantitative with a purposive sampling technique. The data collection technique was carried out by distributing online questionnaires to 100 respondents from Instagram followers of pilihmentor.com. Then analyzed by using the multiple linear regression analysis techniques using SPSS IBM 26. The researcher explained that there were three research results: a) Experiential Marketing variable (X1) had an effect partially significant on purchasing decisions b) Content Marketing variable (X2) partially significant effect on purchasing decisions c) Experiential Marketing and Content Marketing simultaneously have a significant influence.